2022
DOI: 10.11604/pamj.2022.42.132.33344
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic removal of a bullet from the parapharyngeal space just anterior-lateral to the first vertebral body: case report

Abstract: In all head and neck bullet injuries, treatment has to be individualized, as there is no universal protocol for all cases. Five important steps of management should be taken: securing airways, hemorrhage control, recognizing other injuries, foreign body removal when necessary, and repair of facial wounds. In this report, the case of a 28-year-old male patient will be presented and discussed. The patient was referred from a surgery clinic to an ear, nose and throat (ENT) outpatient clinic complaining of right n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…While retaining the foreign body may lead to late migration and even neurological compromise [2], aggressive management may cause collateral iatrogenic injury [3]. Several studies have demonstrated a minimally invasive technique to remove bullets from the cervical spine [4,5]; however, similar procedures for the lumbar spine have rarely been mentioned. Advancements in navigation-assisted surgery have expanded the indications from thoracolumbar pedicle screws to deformity correction and spine tumor resection over the years [6].…”
Section: Introductionmentioning
confidence: 99%
“…While retaining the foreign body may lead to late migration and even neurological compromise [2], aggressive management may cause collateral iatrogenic injury [3]. Several studies have demonstrated a minimally invasive technique to remove bullets from the cervical spine [4,5]; however, similar procedures for the lumbar spine have rarely been mentioned. Advancements in navigation-assisted surgery have expanded the indications from thoracolumbar pedicle screws to deformity correction and spine tumor resection over the years [6].…”
Section: Introductionmentioning
confidence: 99%